2013
DOI: 10.1039/c3sm50708d
|View full text |Cite
|
Sign up to set email alerts
|

Yield stress, thixotropy and shear banding in a dilute aqueous suspension of few layer graphene oxide platelets

Abstract: We demonstrate a rigidity percolation transition and the onset of yield stress in a dilute aqueous dispersion of graphene oxide platelets (aspect ratio $5000) above a critical volume fraction of 3.75 Â 10 À4 with a percolation exponent of 2.4 AE 0.1. The viscoelastic moduli of the gel at rest measured as a function of time indicate the absence of structural evolution of the 3D percolated network of disks. However a shear-induced aging giving rise to a compact jammed state and shear rejuvenation indicating a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
43
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 41 publications
15
43
1
Order By: Relevance
“…The same behavior was later reported by [79] for shear-stress controlled experiments. On the other hand, the transient shear banding phenomenon was not observed by [80] under similar conditions for a yield stress fluid. Ref.…”
Section: Creep Testsmentioning
confidence: 74%
“…The same behavior was later reported by [79] for shear-stress controlled experiments. On the other hand, the transient shear banding phenomenon was not observed by [80] under similar conditions for a yield stress fluid. Ref.…”
Section: Creep Testsmentioning
confidence: 74%
“…Moorcroft et al (111) developed a criterion for the observation of shear banding for such transient flows that solely depends on the shape of the rheological response function. Shear banding has been reported for Carbopol gels (112), clay suspensions (113,114), emulsions and foams (109,115), graphene oxide dispersion (116), and cement pastes (41) in recent reviews including discussions on the physical behavior (108) and probes (67). Recently, Besseling et al (117) reported the presence of shear banding in hard-sphere suspension owing to the concentration variations arising from migration of particles toward domains of low shear rate.…”
Section: Shear Banding and Wall Slipmentioning
confidence: 99%
“…It was reported that the microstructure of materials, the dispersion state and the orientation of plates, and the interaction between plate and matrix affected the rheological properties of plate-like particle suspensions [4][5]. Although the rheological properties of plate-like particle suspensions are widely studied [4][5][6][7][8], some questions still remain unsolved. For example, negative normal stress differences (ΔN) during shear experiments were reported in the concentrated kaolin aqueous solutions [7], clay/polymer suspensions [8] and graphene oxide (GO)/polymer composites [9].…”
Section: Introductionmentioning
confidence: 98%